Entandrophragma: taxonomy and ecology of a genus of African tree species with economic importance. A review - (:unkn) unknown (My University, 2021)
Introduction. Entandrophragma tree species have been the subject of special attention by foresters and scientists for several decades. The purpose of this bibliographic review is to examine the current knowledge acquired on the taxonomy and ecology of this genus in order to identify new research priorities. Literature. The genus Entandrophragma has exclusively African species (10 to 12) that are exploited for the quality of their wood. These species are widespread in the Guineo-Congolese region (6 species) and in the Zambezian and Afromontane regions (5 species). The genus is characterized by a taxonomic evolution that has resulted in an important synonymy of species names (36 to 37). Ecological studies have been carried out on some major commercial species (Entandrophragma angolense, Entandrophragma congoense, Entandrophragma candollei, Entandrophragma cylindricum, Entandrophragma palustre and Entandrophragma utile) in their phytogeographic zones, mainly in the Guineo-Congolese region. Conclusions. Taxonomy and ecology of Entandrophragma tree species typically occurring in woodlands and savannas have been insufficiently studied in comparison with Entandrophragma species occurring in rainforests. Research needs to be developed for the improvement of taxonomic, genetic and ecological knowledge, with a view to formulating appropriate recommendations for the conservation and sustainable management of these species.
Keywords: African Research